2015
DOI: 10.3892/mmr.2015.4101
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-related protein 1 induces angiogenesis by upregulating vascular endothelial growth factor in the synovial fibroblasts of patients with temporomandibular joint disorders

Abstract: Angiogenesis has an important role in the progression of temporomandibular joint disorders (TMD). The aim of the present study was to explore the association between dickkopf-related protein 1 (DKK-1) and angiogenesis in TMD. The expression levels of DKK-1 and vascular endothelial growth factor (VEGF) were quantified by an ELISA assay of the synovial fluid from patients with TMD. The correlation between DKK-1 and VEGF was analyzed by Pearson correlation test. Synovial fibroblasts were isolated from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…It has been suggested that DKK-1 and high-mobility group box 1 (HMGB1) direct the nuclear localization of HIF-1 and thus promote the synthesis of VEGF. 92,93 The growth of nerve endings also plays a role in angiogenesis. Nerve growth factor (NGF), which regulates nerve growth, survival and repair, can stimulate angiogenesis in TMJ osteoarthritis.…”
Section: Angiogenesis Promotes the Development Of Tmj Osteoarthritismentioning
confidence: 99%
“…It has been suggested that DKK-1 and high-mobility group box 1 (HMGB1) direct the nuclear localization of HIF-1 and thus promote the synthesis of VEGF. 92,93 The growth of nerve endings also plays a role in angiogenesis. Nerve growth factor (NGF), which regulates nerve growth, survival and repair, can stimulate angiogenesis in TMJ osteoarthritis.…”
Section: Angiogenesis Promotes the Development Of Tmj Osteoarthritismentioning
confidence: 99%
“…Smadja et al (31) showed that DKK1 enhanced the proangiogenic potential of human endothelial colony-forming cells and these angiogenic effects have been attributed to enhancement of VEGFR2. In addition, Jiang et al (33) showed that DKK1 is correlated with angiogenesis in broblasts through increased expression of VEGF and also found that HIF-1α may be associated with DKK1-induced HUVECs migration. Our data similarly found that DKK1 raised the angiogenic potential of endothelial cells, which was supported by the increased effects of HUVEC invasion, tube formation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of VEGFR2 can initiate multiple signaling pathways that orchestrate a variety of complex biological effects, such as endothelial cell maturation, vessel lumen formation, vascular permeability, vasodilation, angiogenesis, and arteriogenesis [ 25 ]. Thus, it can be hypothesized that high DKK-1 expression results in activation of VEGFR2 expression and increased sensitivity to VEGF in endothelial cells, which is significantly correlated with DKK-1 expression [ 26 ], during coordination of angiogenesis. The above results provide a rationale to support targeting of VEGFR2 using sorafenib, and show the potential of DKK-1 as a target of therapy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%